PEMBUATAN MODEL UJI NILAI TEBAL PARUH (HVL) PESAWAT KONVENSIONAL SINAR-X MENGGUNAKAN PENGOLAHAN CITRA DIGITAL - Hayat Maulana; Suryono Suryono (Youngster Physics Journal, 2013)
Designed of software application half value layer (HVL) which uses digital image processing has been use measurement HVL of X-ray conventional that is designed by using Borland Delphi 7.0 program. The system used as a simple tool for quality control (QC) of output X-ray.The firs step which is done to bring about software application is designing application image cropping, designing application open image, then designing applicationof pixel intensity value and designing application HVL. The step of software application usage is firstly expose phantom stepwedge by using X-ray conventional, secondly, process the expose result so it produces image radiographygray scale, thirdly,process digital imageby using scanner, save image digital with bitmap format, then process image by using software application.From measuring the result of four digital images gray scale obtained HVL average of value is 2.04 mmAl. Beside that, the measurement is also done four time using the standart tool Multipurpose detector (MPD,) obtained HVL average of value is 1,97 mmAL, from both datas it process deviation value 0,07 and relative research is 99,97 % for software application. So it can be conclude that digital image processing can be used to count HVL X-ray conventional. Key words   :Digital image radiography, image cropping, pixel intensity, half value layer (HVL).